The legal challenges of internet addiction among children in Malaysia and Indonesia - Wong, Vatchira Rui Fern; Poppy Putri Hidayani,; Mohd Afiq Danish Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
As one of the most extraordinary means of communication tools, the internet has become one of the fastest growing technology that nearly everyone in the world uses. By the year 2025, there will be 4.41 billion monthly active social media users worldwide. Needless to say, internet has also become one of the biggest threats to the world community, in particular to children users. The presentation of internet addiction which every year increases becomes one of the problems that threatens to not only affecting children's mentality, internet addiction but also, attracting children to cybercrimes such as cyber bullying, online sexual exploitation, pornography, exposure to porn and more. The main issue of this article is whether internet addiction among children poses any legal challenges in curbing this problem. The objective of this article is divided into three parts, namely, to determine the definition of Internet addiction, to understand the legal ramification of internet addiction among children and to analyse the existing laws in Japan, South Korea and China on protecting children against internet addiction and suggestion on improvement that could be made in Malaysia’s and Indonesia’s legal system. The methodology used is doctrinal legal research by referring to books, journals and related articles to obtain data and reading materials in making this article. Based on the research done, in order to adopt and further improve our legislation on internet addiction among children and protecting the children’s welfare, the Malaysian government could take a closer look at the Japan, South Korea and China’s legislation on curbing internet addiction among children.